Clinical aspects of heat-labile and heat-stable toxin-producing enterotoxigenic Escherichia coli: A prospective study among Finnish travellers. Issue 38 (November 2020) - Turunen, Katri; Antikainen, Jenni; Lääveri, Tinja; Kirveskari, Juha; Svennerholm, Ann-Mari; Kantele, Anu
Abstract: Background: Enterotoxigenic Escherichia coli (ETEC) is a major pathogen causing travellers' diarrhoea (TD) among visitors to low- and middle-income countries (LMIC). Scant data are available on rates of travel-acquired ETEC producing heat-labile (LT) and/or heat-stable (ST) toxin or its subtypes, STh (human) and STp (porcine) in various geographic regions, and on clinical pictures associated with each toxin. Methods: Using qPCR, we analysed LT, STh, and STp in stools positive for ETEC in a prospective study among 103 Finnish travellers visiting LMIC. They filled in questionnaires and provided stool samples before and after travel. We scrutinized geographic distribution of LT, STh, and STp ETEC findings, and association between these different ETEC subtypes and moderate/severe TD. Results: Among the 103 stool samples positive for ETEC toxins, the rate for LT was 76%, for STh 26%, and STp 41%. The rate for LT-only was 44%, for STh-only 6%, STp-only 16%, LT + STh 10%, LT + STp 15%, STh + STp 3%, and LT + STh + STp 8%. Findings varied by destination; the rates of LT, STh, and STp were 79%, 21%, and 57%, respectively, in Southern Asia (n = 14); 85%, 10%, and 20% in South-eastern Asia (n = 20); 84%, 13%, and 29% in Eastern Africa (n = 31); and 56%, 50%, and 63% in Western Africa (n = 32), respectively. Of travellers positive for LT, STh, and STp, 83%, 100%, and 88%, encountered TD; 35%, 55%, and 41% reported moderate/severe TD. STh was associated with moderate/severe TD. Conclusions: Toxin findings varied by destination; multiple toxins were commonly detected. Moderate/severe TD was reported most frequently by subjects with STh-ETEC. Highlights: ETEC is a major cause of childhood diarrhoea in LMICs and travellers' diarrhoea among visitors to these destinations. The diarrhoeal symptoms of ETEC are mediated by its LT and ST toxins. ST-toxin is divided into the subtypes STh and STp. This prospective study explored the distribution of ETEC toxins among travellers to various geographic destinations. Toxin findings varied by geographic location. Multiple toxin types proved common. STh was associated with moderate/severe diarrhoea.